ANALISIS HUKUM EKONOMI SYARIAH TERHADAP PRAKTIK JUAL BELI ONLINE (E-COMMERCE) - Panji Marboro; M. Habiburrahman (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The acceleration of digital trade through marketplaces and social media often gives rise to legal anomalies in the form of information asymmetry, which triggers fraudulent product specifications (tadlis) and weakens consumers' bargaining power. The method used by the researchers is a juridical-normative method with a qualitative-literature approach. This research examines the effectiveness of regulations in the realities of non-conventional digital markets. The analysis shows that although the Consumer Protection Law (UUPK) has legally mitigated transaction risks by guaranteeing the right to information and compensation, its efficacy in practice is often reduced by limited state oversight in the social media realm. Herein lies the urgency of this research finding: muamalah fiqh is no longer positioned merely as formal legality, but rather as an internal control system (self-controlling system) for business actors through the supremacy of the values ​​of ṣidq (honesty) and amanah (trustworthiness). Islamic law rigidly eliminates digital transactions contaminated with quality gharar in order to restore market balance. The theoretical implications of this research offer a new paradigm that comprehensive digital consumer protection cannot rely solely on positive legal sanctions but must be integrated with the reconstruction of Islamic transactional morality. While many previous studies have focused solely on the formal validity of cyber contracts or the weaknesses of secular law enforcement.